A meta-analysis of epigenome-wide association studies of ultra-processed food consumption with DNA methylation in European children - Joana Llauradó-Pont; Nikos Stratakis; Giovanni Fiorito; Evangelos Handakas; Alexander Neumann; Henrique Barros; Anne Lise Brantsæter; Kiara Chang; Leda Chatzi; Janine F. Felix; Regina Grazuleviciene; Vincent W. V. Jaddoe; et al. (Clinical Epigenetics)
Abstract Background/objective There is limited knowledge on how diet affects the epigenome of children. Ultra-processed food (UPF) consumption is emerging as an important factor impacting health, but mechanisms need to be uncovered. We therefore aimed to assess the association between UPF consumption and DNA methylation in children. Methods We conducted a meta-analysis of epigenome-wide association studies (EWAS) from a total of 3152 children aged 5–11 years from four European studies (HELIX, Generation XXI, ALSPAC, and Generation R). UPF consumption was defined applying the Nova food classification system (group 4), and DNA methylation was measured in blood with Illumina Infinium Methylation arrays. Associations were estimated within each cohort using robust linear regression models, adjusting for relevant covariates, followed by a meta-analysis of the resulting EWAS estimates. Results Although no CpG was significant at FDR level, we found suggestive associations (p-value < 10–5) between UPF consumption and methylation at seven CpG sites. Three of them, cg00339913 (PHYHIP), cg03041696 (intergenic), and cg03999434 (intergenic), were negatively associated, whereas the other four, cg14665028 (NHEJ1), cg18968409 (intergenic), cg24730307 (intergenic), and cg09709951 (ATF7), were positively associated with UPF intake. These CpGs have been previously associated with health outcomes such as carcinomas, and the related genes are mainly involved in pathways related to thyroid hormones and liver function. Conclusion We only found suggestive changes in methylation at 7 CpGs associated with UPF intake in a large EWAS among children: although this shows a potential impact of UPF intake on DNAm, this might not be a key mechanism underlying the health effects of UPFs in children. There is a need for more detailed dietary assessment in children studies and of intervention studies to assess potential epigenetic changes linked to a reduction in UPF in the diet. Graphical abstract